Improving Students’ Reading Comprehension Through Listen-Read-Discuss (LRD) Strategy - Tawali, Tawali (Jurnal Paedagogy, 2021)
This research aimed at finding out whether Listen-Read-Discuss (LRD) strategy improves students’ reading comprehension or not. The research was a classroom action research. The data collected through quantitative and qualitative approach. Quantitative data was gained from the result of pre-test and post-test from reading test. Meanwhile, qualitative data was gained from the result of observation sheets toward students’ and teachers’ activity. The instruments used by the researcher were test and observation sheet. The finding of the research showed that the strategy Listen-Read-Discuss improve the students’ reading comprehension in descriptive text. The improvement can be seen from the mean score of students from pre-test, post-test one, and post-test two. The mean score of pre-tests was 64.46 (50%), there were eight students who passed the minimum passing grade, in the post-test one, 75.35 (67%), twelve students passed the minimum passing grade and in the post-test two, 82.14 (89%), twenty-five students passed the minimum passing grade (KKM).